Facile synthesis of low dimensional CuO nanostructures and their gas sensing applications. Issue 2 (21st January 2016) - Bhuvaneshwari, S.; Gopalakrishnan, N.
Abstract : Morphology controlled Cr doped CuO nanostructures were synthesized by hydrothermal method. Morphological evolution from rod‐like (pure) to sheet (4 at.% Cr) and boat‐like (8 at.% Cr) structures were observed. The 8 at. % Cr doped CuO nano‐boats showed enhanced gas sensitivity owing to their larger surface area. Abstract : A simple and cost effective hydrothermal method has been employed to synthesis morphology controlled pure and Cr doped (4 and 8 at. %) CuO nanostructures. Crystalline purity and structure of the nanostructures were validated by X‐ray diffraction and Retvield analyses. Field emission scanning electron microscopy revealed the evolution of rod‐like, sheet‐like and boat‐like morphologies for pure, 4 and 8 at. % Cr doped CuO nanostructures respectively. The optical band gap estimated using the K‐M function plot from diffused reflectance spectroscopy showed a shift in band gap from 1.68 to 1.90 eV with respect to Cr concentration. The synthesized CuO nanostructures were investigated for the efficient room temperature gas sensing of ammonia, ethanol and methanol vapours under different concentrations (100‐600 ppm). The 8 at. % Cr doped CuO nano‐boats showed enhanced gas sensitivity than other CuO nanostructures owing to their typical morphology, larger surface area and related properties.